Finite element analysis of helical staircase using ansys software - Siti Zulaikha, Ahmad Hamizan (2013)
This research deals with the analysis of helical staircase based on finite element method using ANSYS software. Helical staircase is just a type from many type of staircase that has been designed and used nowadays. Helical stair has an open well at the center which is a continuous slab staircase without a central core. A helical is warped surface generated by a line wrapped around a central imaginary core. It will be like the curve of a screw. The slab is like inclined plane. It can be circular or elliptical (it has no central structure). There are many researches done to analyze concrete shell using finite element method. From the researches, all the steps of calculation that included formulas to analyze the helical staircase can be found. Using ANSYS software has resulted in considerable advances in the analysis and design of any structures. While by determining the design of three-dimensional using Finite Element Analysis Method (FEM) with the use of matrix equations consist of global displacement matrix and also strain displacement matrix. Because all of these methods are based on simplified analysis, they cannot provide the engineer with all the desired design information and only provide the engineer with all the desired design information and only provide very limited indications. To analyze the design of the helical stair, ANSYS software will be used. From the research study, two cases of study with five models have been design in order to compare and manage the results. The case 1 is where two model has been design with the reasons are to study the effect of different central angle to the helical staircase in terms of deflection and stress distribution. The obtained results for case 1 has proven that the least of central angle for degree of rotation will caused deflection and stress distribution results decrease also. While for the case 2, three models with different size of waist thickness has been create in order to complete the study of effect of waist thickness effect to helical staircase in terms of deflection and stress distribution. From the results obtained, it has been prove that, the greater size of waist thickness of helical staircase, the decrease the value in terms of deflection and stress distribution.